Biological characteristics and pathogenicity comparison of Nocardia seriolae isolated from Micropterus salmoides and Channa argus - Zhang, Wei; Zhou, Kexin; Huang, Lei; Yang, Na; Lin, Lingyun; Chen, Lu; Yao, Jiayun; Dong, Mingxin; Shen, Jinyu; Pan, Xiaoyi (Frontiers in Veterinary Science, 2024)
Nocardia seriolae is the primary pathogen causing main pathogen of nocardiosis in various fish species, and leads to significant economic losses in the aquaculturefish industry. In this study, ten bacterial strains strains of bacteria, isolated from Micropterus salmoides and Channa argus which were infected with nocardiosis, were identified as N. seriolae by physiological and biochemical identification, as well as 16S rDNA sequencing. MoreoverFurthermore, the key virulence-related genes such as ESX-1, T7SS-2, T7SS-3, EspG1, sodC, sod2 and ESAT6 were all positive, and showing high homology among different strains.the same virulence gene in different strains exhibits very high homology.their sequences were consistent. Pathogenicity testing revealed mortality rates ranging from 70% to 100%, accompanied by the presence of white nodules in the viscera of deceased fish. The drug sensitivity test demonstrated that LY21811, the most lethal strain among all strains, exhibited high sensitivity to nine types of antibiotics, including azithromycin, doxycycline, florfenicol and compound sulfamethoxazole, yet showed complete resistance to β-lactam antibiotics. Additionally, the tannic acid also demonstrated potent inhibitory effects against LY21811, with a minimum inhibitory concentration of 0.0625 mg/mL. These results showed that N. seriolae originated from M. salmoides and C. argus in Zhejiang ProvinceChina were highly conserved, demonstrating a high homogeneity in genetic characteristics, pathogenicity and antimicrobial susceptibilities. The aboveThese results provide a foundation offor further research on the pathogenic characteristics and disease prevention of N. seriolae infections.